Xanthogranulomatous Pyelonephritis: An Uncommon Case Report Mimicking Sarcomatoid Renal Cell Carcinoma - Agrawal, Ruchi; Singh, Kulwant; ., Parul; Hooda, Sunaina; Rana, Parveen; Saluja, Swaran Kaur (Annals of Pathology and Laboratory Medicine, 2024)
Introduction: Xanthogranulomatous pyelonephritis (XGP) is an atypical form of chronic pyelonephritis characterized by the destruction of renal parenchyma and its replacement with a chronic inflammatory infiltrate of xanthoma cells. Case Report: A 46-year-old male presented in the surgery outpatient department with abdominal pain and recurrent fever. Contrast-enhancing computed tomography (CECT) revealed a lobulated, irregularly shaped, heterogeneously enhancing lesion in the left kidney arising from the upper pole with mitotic activity. Left total nephrectomy was performed, and the specimen was sent for histopathology. The specimen measured 12x8.5x5.3cm. Grossly, a globular mass lesion measuring 9x7x2.4 cm was observed at the upper pole of the kidney. On cutting, an unencapsulated grey-white solid mass with ill-defined margins was identified in the upper pole of the kidney. Microscopically, sheets and bundles of oval to spindle-shaped cells amidst chronic inflammatory infiltrate and giant cells were seen. These cells exhibited moderate pleomorphism with large vesicular nuclei, irregular nuclear margins, clumped chromatin, and pale to eosinophilic ample cytoplasm. Immunohistochemistry (IHC) revealed strong positivity for both vimentin and CD68 and negativity for cytokeratin, CD10, and desmin. The final diagnosis of XGP was made. Conclusion: XGP has earned the title of the "great imitator" due to its overlapping gross and microscopic features with renal cell carcinoma (RCC). This overlap often leads to a delay in reaching a specific diagnosis. However, immunohistochemistry (IHC) helps to avoid such misdiagnoses in the majority of cases.